2013
DOI: 10.1371/journal.pone.0081347
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Gab1 Inhibits Cell Proliferation and Migration in Hilar Cholangiocarcinoma

Abstract: Hilar cholangiocarcinoma is a highly aggressive malignancy originating from the hilar biliary duct epithelium. Due to few effective comprehensive treatments, the prognosis of hilar cholangiocarcinoma is poor. In this study, immunohistochemistry was first used to detect and analyze the expression of Gab1, VEGFR-2, and MMP-9 in hilar cholangiocarcinoma solid tumors and the relationships to the clinical pathological features. Furthermore, Gab1 and VEGFR-2 siRNA were used to interfere the hilar cholangiocarcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…Gab1, VEGFR-2, and MMP-9 are significantly overexpressed in primary intrahepatic cholangiocarcinoma tissues, and the VEGFR-2/Gab1/PI3K/Akt pathway is able to regulate the malignant biological behaviors [i.e., growth, apoptosis, and invasion] in an intrahepatic cholangiocarcinoma cell line. As a multisubstrate adapter protein, Gab1 upregulates proto-oncogene expression via amplification of signaling pathways related to tumorigenesis [11][12][13][14]. Using immunohistochemistry, we found high expression of Gab1 in intrahepatic cholangiocarcinoma tissues from 24 patients and demonstrated that Gab1 was correlated with lymphatic metastasis and TNM stage.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Gab1, VEGFR-2, and MMP-9 are significantly overexpressed in primary intrahepatic cholangiocarcinoma tissues, and the VEGFR-2/Gab1/PI3K/Akt pathway is able to regulate the malignant biological behaviors [i.e., growth, apoptosis, and invasion] in an intrahepatic cholangiocarcinoma cell line. As a multisubstrate adapter protein, Gab1 upregulates proto-oncogene expression via amplification of signaling pathways related to tumorigenesis [11][12][13][14]. Using immunohistochemistry, we found high expression of Gab1 in intrahepatic cholangiocarcinoma tissues from 24 patients and demonstrated that Gab1 was correlated with lymphatic metastasis and TNM stage.…”
Section: Discussionmentioning
confidence: 87%
“…VEGFR-2 is critical for VEGF-mediated tumor angiogenesis and lymphangiogenesis [18,19], and its expression is associated with tumor invasion and metastasis [14,20,29,30]. A VEGFR-2 antagonist can significantly inhibit VEGFinduced tumor growth and metastasis [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported, Gab1 can up-regulate the proto-oncogene expression through interactions with Grb2, protein-tyrosine phosphatase SHP2, phosphatidylinositol 3-kinase (PI3K) and phosphatidylinositol (3,4,5)-trisphosphate (PIP3), therefore it plays an important role in the tumor development and progression (Oka et al 2008;Wohrle et al 2009;Felici et al 2010). Although there have been several studies demonstrated that Gab1 is involved in the development of chondrosarcoma (Fan et al 2016), cholangiocarcinoma (Sang et al 2013(Sang et al , 2015, colorectal cancer (Seiden-Long et al 2008) and mammary tumor (Gillgrass et al 2003), there are no published reports describing the correlation between Gab1 and the biological behaviors of EOC.…”
Section: Introductionmentioning
confidence: 98%